Association of sleep duration with Visceral Adiposity Index: a cross-sectional study based on the NHANES 2007–2018 - Jing Zhang; Juan Liu; Xingkang He; Yajie Gao; Nan Ye (BMJ Open)
Objective We aimed to assess the associations between sleep duration and Visceral Adiposity Index (VAI).Design Cross-sectional study.Setting The National Health and Nutrition Examination Survey (2007–2018).Participants A total 11 252 eligible participants who have complete information for sleep duration and VAI.Outcome measure The VAI index, which is sex-specific and takes into consideration factors such as waist circumference, body mass index, high-density lipoprotein cholesterol and triglycerides, was calculated in accordance with prior research. Multiple linear regressions and subgroup analyses were employed to evaluate the connection between the duration of sleep and the VAI.Results The mean sleep duration and VAI of included participants were 7.05 hours/day and 2.03, respectively. After adjusting for the sociodemographic, lifestyle and other covariates, short sleep was significantly linked to increased VAI (β=0.15, 95% CI 0.01 to 0.28) in relation to middle sleep duration, whereas no significant association was found between long sleep duration and VAI. An L-shaped relationship was observed between sleep duration and VAI. When sleep duration was less than 7.5 hours/day, a negative association between sleep duration and VAI was obvious. However, when sleep duration was >7.5 hours/day, VAI was increased with a longer sleep duration, although it was not significant.Conclusions An L-shaped relationship was observed between sleep duration and VAI, with insufficient sleep, being independently linked to a higher VAI. This implies that sleep deprivation might be associated with visceral adipose distribution and disfunction.